Implementasi Manajemen Pada Pendaftaran Ibadah Haji Di Kantor Kementerian Agama Bukittinggi - Novsya Putri Eka Yani; Zulhelmi Zulhelmi (CV. ALIM'SPUBLISHING, 2024)
Abstract. Implementation of management for Hajj pilgrimage registration at the Bukittinggi Ministry of Religion Office. The Hajj pilgrimage is a religious obligation for Muslims who meet the requirements. The Bukittinggi Ministry of Religion Office is responsible for providing the best service in organizing the Hajj. The main problem is a lack of understanding in the process of registration, payment and cancellation of the Hajj. The administrative process includes registration, payment and cancellation. Planning is carried out for services, guidance before, during and after the Hajj. The organization at the Bukittinggi Ministry of Religion Office has a clear structure for managing the registration process. Mobilization and supervision are also implemented to ensure effectiveness and efficiency in achieving goals. This research aims to determine the Management Implementation of Hajj Registration at the Bukittinggi Ministry of Religion Office. In this research the author used qualitative-descriptive research. The author uses data collection methods through observation, interviews, documentation. Based on the research results, it can be concluded that it shows that management implementation has resulted in significant improvements in the Hajj registration process, such as increasing efficiency, data accuracy and service to pilgrims. Findings also identify factors that support successful implementation, such as effective communication and strong managerial support, as well as challenges faced, such as limited resources and regulatory changes. In conclusion, the implementation of management in Hajj registration at the Bukittinggi Ministry of Religion Office has brought significant improvements and made a positive contribution to the efficiency and quality of services.